Core-composite mediated separation of diverse nanoparticles to purity. Issue 39 (13th September 2019) - Bhatt, Chandra S.; Nagaraj, Bharathkumar; Ghosh, Deepanjan; Ramasamy, Sureshkumar; Thapa, Ranjit; Marpu, Sreekar B.; Suresh, Anil K.
Abstract : A generalized method for sorting nanoparticles based on their cores does not exist; it is an immediate necessity, and an approach incorporating cost-effectiveness and biocompatibility is in demand. Abstract : A generalized method for sorting nanoparticles based on their cores does not exist; it is an immediate necessity, and an approach incorporating cost-effectiveness and biocompatibility is in demand. Therefore, an efficient method for the separation of various mixed core-compositions or dissimilar metallic nanoparticles to their pure forms at the nano-bio interface was developed. Various simple core-combinations of monodispersed nanoparticles with dual cores, including silver plus gold, iron oxide plus gold and platinum plus gold, to the complex three-set core-combinations of platinum plus gold plus silver and platinum plus iron plus gold were sorted using step-gradient centrifugation in a sucrose suspension. Viscosity mediated differential terminal velocities of the nanoparticles permitted diversified dragging at different gradients allowing separation. Stability, purity and properties of the nanoparticles during separation were evaluated based on visual confirmation and by employing advanced instrumentations. Moreover, theoretical studies validated our experimental observations, revealing the roles of various parameters, such as the viscosity of sucrose, the density of the particles and the velocity and duration of centrifugation, involved during the separation process. This remarkably rapid, cost-efficient and sustainable strategy can be adapted to separate other cores of nanoparticles for various biomedical research purposes, primarily to understand nanoparticle induced toxicity and particle fate and transformations in natural biotic environments.